2020
DOI: 10.1093/mnras/staa625
|View full text |Cite
|
Sign up to set email alerts
|

The white dwarf planet WD J0914+1914 b: barricading potential rocky pollutants?

Abstract: An ice giant planet was recently reported orbiting white dwarf WD J0914+1914 at an approximate distance of 0.07 au. The striking non-detection of rocky pollutants in this white dwarf's photosphere contrasts with the observations of nearly every other known white dwarf planetary system. Here, I analyze the prospects for exterior extant rocky asteroids, boulders, cobbles and pebbles to radiatively drift inward past the planet due to the relatively high luminosity (0.1L ⊙ ) of this particularly young (13 Myr) whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Instead, rocky particles external to the planet could have any orbital eccentricity or inclination. These values may or may not have been radiatively damped through the relatively high luminosity (≈ 0.1L ) of this white dwarf (Veras 2020) and could be at any stage of damping.…”
Section: The Particlesmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, rocky particles external to the planet could have any orbital eccentricity or inclination. These values may or may not have been radiatively damped through the relatively high luminosity (≈ 0.1L ) of this white dwarf (Veras 2020) and could be at any stage of damping.…”
Section: The Particlesmentioning
confidence: 98%
“…Both the extent of the gas disc as well as the lack of rocky debris motivate dynamical questions about the role of the planet, denoted as WD J0914+1914 b, in shaping the system. Veras (2020) found that WD J0914+1914 b acts as an effective barricade for pebbles and most boulders which are radiatively dragged towards the white dwarf. However, he only sampled parameter space which was relevant to those bodies and considered only radiative drag and one type of planet.…”
Section: Introductionmentioning
confidence: 99%
“…According to various arguments in Section 2.2 of Malamud et al (2021), the initial size of tidal fragments falls exactly within that range. However, better theoretical understanding of the seasonal Yarkovsky orbital shrinking effect in highly eccentric orbits is still required (Veras et al 2015a(Veras et al , 2019Veras 2020).…”
Section: Radiation Effectsmentioning
confidence: 99%
“…Instead, the planet's current location my be explained by a previous gravitational scattering event within the system, or from a dissipative capture from an external companion or cluster. In contrast, the close separations of WD J0914+1914 b and WD 1856+534 b require either (i) a gravitational scattering event during the white dwarf phase, plus some form of tidal shrinkage (Muñoz & Petrovich 2020;O'Connor, Liu & Lai 2021;Veras & Fuller 2020;Veras 2020;Zotos et al 2020;Stephan, Naoz & Gaudi 2021), or (ii) survival of the planet within a common envelope of the white dwarf precursor (Chamandy et al 2021;Lagos et al 2021).…”
Section: Major Planetsmentioning
confidence: 99%